Explaining the Low US Inflation - Coincidence or "New Economy"? Evidence Based on a Wage-Price Spiral - Carl Andreas Claussen; Karsten Staehr (Norges Bank, 2001)
We study possible factors behind the subdued inflation in the United States since the mid-1990s. A standard expectations-augmented Phillips curve does not exhibit structural breaks. However, a wage-price spiral comprising wage growth, consumer price inflation and producer price inflation shows an otherwise unexplained downward shift in CPI inflation since the mid-1990s. We estimate this downward shift to be approximately 1 percentage point since 1994. The result emerges in spite of a large number of explanatory variables and seems to reflect deep structural changes of the economy. Counterfactual simulation of the wage-price spiral shows that the low level of U.S. inflation during the late 1990s stems from coincidental favourable shocks as well as factors that may reflect new economy developments.
hdl:11250/2498707
Keywords: C32; E31; E37; 330; inflation; wage-price spiral; unemployment; productivity